THE INFLUENCE OF FINANCIAL LITERACY AND INCOME PERCEPTION ON INVESTMENT DECISIONS OF MUTUAL FUNDS IN MANAGEMENT PROGRAM REGULAR CLASS FACULTY OF ECONOMICS AND BUSINESS NATIONAL UNIVERSITY WITH GENDER AS A CONTROL VARIABLE - Ganang Ari Putranto; Kumba Digdowiseiso (Jurnal Ekonomi, 2023)
The purpose of this research is to analyze the effect of financial literacy and perceived income on investment decisions in students of management program Faculty of Economics and Business National University. This research is sourced from primary data obtained from respondents through the distribution of questionnaires. The research sample was 100 respondents with the method used was simple random sampling method. Descriptive analysis and multiple linear regression analysis are data analysis techniques used in this study with the STATA Statistics version 16 program. The results show that the effect of financial literacy and perceived income on investment decisions variables have a positive and significant, on investment decisions in management study program students, Faculty of Economics and Business, National University.